Projected Destination Images Versus Visitor-Generated Visual Content in Brasov, Transylvania - Nechita, Florin; Demeter, Robert; Briciu, Victor-Alexandru; Varelas, Sotiris; Kavoura, Androniki (Springer International Publishing, 2019)
Visitor-generated visual content (VGVC) that is created and uploaded as travel photos allows researchers to examine tourists’ behavior, as traditional tourism data collection methods (surveys, interviews and focus groups) were proved both expensive and time consuming. Tourists take photos, upload them to social networks and photo sharing platforms, leaving digital footprints on the Internet, footprints that can be subsequently used for tourism research. Photos tagged with “Brasov” between January 1st 2000 and July 1st 2018 were collected using Flickr API. A collection of 22,362 geotagged photos collected from Flickr was analyzed. Using DBSCAN algorithm, tourist attraction areas were identified, after eliminating the content created by people living permanently in the area. For detailed data analysis seasonal graphs were generated. The research method combines content analysis based on text tags and image data with structural analysis based on geospatial data. The resulting tourist attractions of the area as derived from the number of photos taken there were compared to the distribution of the attractions as resulted from Destination Management Organizations’ (DMOs) promotional materials. The spatial patterns of tourist activity in Brasov revealed many similarities and differences compared to promoted attractions by the DMOs. The results indicate that geo-tagged photos in Brasov reflect the projected image of the destination as the data provided a hotspot distribution of popular tourist attractions. This paper explores the advantages of using VGVC for tourism research, but also highlights the limitations that have to be addressed. Implications for tourism marketing managers are provided thereafter.
Keywords: visitor-generated visual content; geotagged photos; projected destination image